Combinational light emitting diode-high frequency focused ultrasound treatment for HeLa cell. (31st October 2017) - Choe, Se-Woon; Park, Kitae; Park, Chulwoo; Ryu, Jaemyung; Choi, Hojong
Abstract: Purpose: Light sources such as laser and light emitting diode or ultrasound devices have been widely used for cancer therapy and regenerative medicines, since they are more cost-effective and less harmful than radiation therapy, chemotherapy or magnetic treatment. Compared to laser and low intensity ultrasound techniques, light emitting diode and high frequency focused ultrasound shows enhanced therapeutic effects, especially for small tumors. Materials and methods: We propose combinational light emitting diode-high frequency focused ultrasound treatment for human cervical cancer HeLa cells. Individual red, green, and blue light emitting diode light only, high frequency focused ultrasound only, or light emitting diode light combined with high frequency focused ultrasound treatments were applied in order to characterize the responses of HeLa cells. Results: Cell density exposed by blue light emitting diode light combined with high frequency focused ultrasound (2.19 ± 0.58%) was much lower than that of cells exposed by red and green light emitting diode lights (81.71 ± 9.92% and 61.81 ± 4.09%), blue light emitting diode light (11.19 ± 2.51%) or high frequency focused ultrasound only (9.72 ± 1.04%). Conclusions: We believe that the proposed combinational blue light emitting diode-high frequency focused ultrasound treatment could have therapeutic benefits to alleviate cancer cell proliferation